Investigation of control region sequences of mtDNA in a Chinese Maonan population. (4th May 2017) - Meng, Jing-Hua; Yao, Jun; Xing, Jia-Xin; Xuan, Jin-Feng; Wang, Bao-Jie; Ding, Mei
Abstract: DNA sequences in the control region of mitochondrial DNA (mtDNA) were investigated in 206 unrelated individuals living in Huanjiang Maonan Autonomous County in the People's Republic of China. DNA was extracted from blood-stained filter papers. Hypervariable regions, including HVI and HVII, were amplified and sequenced and sequences aligned and compared with the revised Cambridge sequence (rCRS). One hundred and seventy-two polymorphic sites were identified that defined 170 haplotypes. Of these, 143 were unique and 27 were shared by more than one individual. Genetic diversity was estimated to be 0.9977 (± 0.0008), and the random match probability was 0.71%. The proportions of macro-haplogroups R*, M*, N*, D, U, R0, L3*, and L* were 50.49%, 26.21%, 11.17%, 3.88%, 3.88%, 2.43%, 1.46%, and 0.49%, respectively. Additionally, phylogenetic comparison and principal component analysis (PCA) demonstrated that Chinese Maonans shared a close genetic relationship with the Gelao ethnic community in Laos and China. These results may be useful in future human genetic studies and forensic examinations.